Analisis Kepemimpinan Pendidikan Islam Abad Pertengahan dan Penetrasinya terhadap Renaisans di Eropa - Indriarti, Tiara; Yusuf Hanafiah; Fadhlurrahman, Fadhlurrahman (Kuras Institute, 2024)
Purpose − This research aims to understand the state of Europe before the Renaissance, describe the process of the Renaissance, and analyze the penetration of Islamic education to the Renaissance movement in Europe. Method − This research is qualitative type with a library research approach. Where research was carried out by collecting, reading and reviewing books related to the analysis of Islamic educational leadership and its penetration into the renaissance in Europe. The analysis techniques in collecting data for this research are data reduction, data presentation, and drawing conclusions using a historical approach. Findings − The results of this study describe the condition of Europeans before the renaissance, the process of the renaissance, and the analysis of the contribution of Islamic education to the renaissance movement in Europe. The condition of Europe before the Renaissance experienced dark ages, moral degradation, and ignorance (dark ages). The dark ages of Europeans can be seen from economic, political, socio-cultural, and religious aspects. The process of the renaissance was motivated by the Muslims who occupied the Andalusian region (Spain) in 771 AD under the caliphate of the Umawid State, namely Al-Walid bin Abdul Malik and the governor of North Africa Musa bin Nushair and commanders Tharif bin Malik and Thariq bin Ziyad. Andalusia (Spain) developed under the leadership of the Umawid State and the Abbasid State which carved a glorious civilization. Muslim scientists were born, one of which was Ibn Rushd, for his thoughts was born the bluff of Averroeism. The Renaissance first appeared in Italy by the bourgeoisie and the word renaissance was first introduced in France by Jules Michelet and popularized by Jacob Burckhardt. On the other hand, the renaissance also began with the Rusydian movement (students of Ibn Rushd) from among the Westerners themselves, among them Musa Ibn Maimun and Siger de Barbant. The contribution of Islamic Education to the renaissance can be seen from the existing education system or level of education such as, kuttab, mosque, book translation center and library. Where it made a long-term contribution to the renaissance process.